Bilten Instituta za proučavanje folklora u Sarajevu = Bulletin of Institute for Folklore Studies Sarajevo. (Sarajevo : Institute for Folklore Studies, 1951)
Bibliotheek Camille Huysmans
Servo-Kroatisch
Periodiek
Keywords: volksmuziek; folklore; Bosnië-Herzegovina.